Topical Application of Olive Oil and Aloe Vera Gel on Pregnant Women's Striae Gravidarum - Intanwati Intanwati; Dyah Ayu Wulandari; Fauziah Winda Gurnita (JURNAL KEBIDANAN, 2022)
One of the physical changes that often occur in 50-90% of pregnant women is the appearance of striae gravidarum. Striae gravidarum is caused by stretching of the skin during pregnancy.  The impact is a decrease in confidence, itchy, hot, and dry sensations, and cause emotional distress that can interfere with pregnancy. Olive oil and Aloe vera gel are good natural ingredients for skincare. The purpose of this study was to find out the effectiveness of the topical application of Olive oil and Aloe vera gel against the incidence of pregnant women’s striae gravidarum in the Working Area of Puskesmas Kedungmundu 2020. This research was a quantitative study with a quasi-experiment control group design with pretest-posttest. Sampling techniques use purposive sampling. The results of bivariate olive oil analysis with the Wilcoxon test showed P-value (0.647 α 0.05), so there was no effect of topical application of olive oil on the incidence of striae gravidarum.  The results of bivariate analysis of Aloe vera gel with Wilcoxon test showed a P-value (0.642 α 0.05), so there was no effect of topical application of Aloe vera gel on the incidence of striae gravidarum. Based on the Independent Test T-Test the difference between the two groups pre-post obtained P-value (1 α 0.05), then there was no difference in the effectiveness of the topical application of olive oil and aloe vera gel to the incidence of striae gravidarum in pregnant women in The Region of Puskesmas Kedungmundu 2020.